2018
DOI: 10.29333/ajqr/5796
|View full text |Cite
|
Sign up to set email alerts
|

Gangs and environment: A comparative analysis of prison and street gangs

Abstract: One misconception in gang research is the assumption that prison gangs and street gangs are organizationally and ideologically synonymous. Although in the minority, some researchers suggest that prison gangs are qualitatively and quantitatively different from other gangs (Fleisher & Decker, 2001). Utilizing 30 in-depth semi-structured interviews with formerly incarcerated gang members in the New England area, this article assesses the effect of environment on the organizational structure, ideologies, and pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…For this reason, individuals with PTSD often indicate that they lack feelings of secureness and safety (Fullerton et al, 2015; Grieger et al, 2004). Gangs are often cited by members as being protective and providing such a sense of safety (Ortiz, 2019; Skarbek, 2012; Sobel & Osoba, 2009). While this may be somewhat counterintuitive because of the increased risk for exposure to violence that gang members face (Gilman, et al, 2017; Miller, 2001; Peterson et al, 2004), it is still identified by gang members as a major reason why gangs present a functional option for individuals with PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, individuals with PTSD often indicate that they lack feelings of secureness and safety (Fullerton et al, 2015; Grieger et al, 2004). Gangs are often cited by members as being protective and providing such a sense of safety (Ortiz, 2019; Skarbek, 2012; Sobel & Osoba, 2009). While this may be somewhat counterintuitive because of the increased risk for exposure to violence that gang members face (Gilman, et al, 2017; Miller, 2001; Peterson et al, 2004), it is still identified by gang members as a major reason why gangs present a functional option for individuals with PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, female teachers are said to be more likely to practice student-centered teaching and highlight feminine characteristics such as being caring and supportive towards students (Ambusaidi & Al-Farei, 2017). In fact, Oritz (2018) argued that female teachers are more likely to be involved in interpersonal behaviour and close relationships, thus contributing to fostering a sense of belonging amongst students. In contrast, male teachers generally have a competitive and achievement-oriented behavioral nature.…”
Section: Factors Affecting Teachers' Teaching Stylesmentioning
confidence: 99%
“…The internet reduces the need for an open-air illegal drug market as well as allows for organized prostitution to solicit electronically (New Jersey Commission on Investigation, 2000). Gangs have been documented to actively recruit new members using the internet and social media (New Jersey Commission on Investigation, 2000;Ortiz, 2018). The Nigerian 419 fraud is a successful type of fraud that shows how easy it is for motivated criminals to find a large number of potential victims since it is estimated that the Nigerian 419 fraud takes $3 billion a year from victims (Durkin, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%